Contemporary Christian Serpent Handlers And The New Paradigm For The Psychology Of Religion - Jr, Ralph W. Hood (Research in the social scientific study of religion, 2008)
The widely acknowledged call for a new multilevel interdisciplinary paradigm for the psychology of religion is illustrated by a survey of our research on the contemporary Christian serpent handlers of Appalachia. Over a fifteen year period, we have employed a variety of methodologies and levels of analysis to explore the history of this tradition. They included archival documentation of the early endorsement of the Church of God for this ritual as well as the role of the Gospel of Mark within Pentecostal denominations that eventually rejected this ritual. We collected oral histories of this tradition and explored the meaning that handling has for believers using phenom-enological interviews and hermeneutical methods of exploring the thematic structure of not only handling, but also of the anointing, and of near-death experiences from serpent bites. We also have developed an empirically based formula for probability of bites based upon video taped documentations of handling that we have archived. In addition, we explored the legal history of laws against handling as well the reasoning that judges gave for upholding bans against serpent handling on appeals to state supreme courts. In quasi experimental studies we explored both rational rejection of this practice and the influence of personal and cultural prejudice against it. We also empirically demonstrated that attitudes toward both handlers and laws banning the practice could be changed based upon exposure to handlers’ own justification for their beliefs and practices. Finally, we explored the symbolic and sign value of the serpent indicating how their confluence produces an intense emotional response that is viewed as holy by this tradition.